2011
DOI: 10.1002/mma.1569
|View full text |Cite
|
Sign up to set email alerts
|

Decay property of Timoshenko system in thermoelasticity

Abstract: We investigate the decay property of a Timoshenko system of thermoelasticity in the whole space for both Fourier and Cattaneo laws of heat conduction. We point out that although the paradox of infinite propagation speed inherent in the Fourier law is removed by changing to the Cattaneo law, the latter always leads to a solution with the decay property of the regularity‐loss type. The main tool used to prove our results is the energy method in the Fourier space together with some integral estimates. We derive L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…They proved that heat dissipation alone is sufficient to stabilize the system in both cases and then concluded that the Timoshenko–Fourier and the Timoshenko–Cattaneo systems have the same decay rate, which depends on a certain stability number (which is a function of the parameters of the system) as identified previously by Santos et al in for Timoshenko system in a bounded domain. See also and for similar results. For more papers related to the second sound, we refer the reader to , and the references thereinIn this present work, we consider {ρ1φttκφx+ψx+σθx=0,in(0,1)×(0,),ρ2ψttbψxx+κφx+ψ=0,in(0,1)×(0,),ρ3θt+qx+σφxt=0,in(0,1)×(0,),τqt+q+γθx=0,in(0,1)×(0,),φ(x,0)=φ0(x),φt(x,0)=φ1(x),θ(x,0)=θ0(x),in(0,1),ψ(x,0)=ψ0(x),ψt(x<...>…”
Section: Introductionsupporting
confidence: 63%
“…They proved that heat dissipation alone is sufficient to stabilize the system in both cases and then concluded that the Timoshenko–Fourier and the Timoshenko–Cattaneo systems have the same decay rate, which depends on a certain stability number (which is a function of the parameters of the system) as identified previously by Santos et al in for Timoshenko system in a bounded domain. See also and for similar results. For more papers related to the second sound, we refer the reader to , and the references thereinIn this present work, we consider {ρ1φttκφx+ψx+σθx=0,in(0,1)×(0,),ρ2ψttbψxx+κφx+ψ=0,in(0,1)×(0,),ρ3θt+qx+σφxt=0,in(0,1)×(0,),τqt+q+γθx=0,in(0,1)×(0,),φ(x,0)=φ0(x),φt(x,0)=φ1(x),θ(x,0)=θ0(x),in(0,1),ψ(x,0)=ψ0(x),ψt(x<...>…”
Section: Introductionsupporting
confidence: 63%
“…We refer to [12,13,16] for frictional dissipation case, [5,14,15] for thermal dissipation case, and [1,2,8,9] for memory-type dissipation case.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on the dissipative Timoshenko system can be found in the literature. We refer to [20,21] for frictional dissipation case, [8,25,26] for thermal dissipation case, and [1,3,13,14] for memory-type dissipation case.…”
Section: Known Resultsmentioning
confidence: 99%